Preferensi Petani dalam Memilih Varietas Bawang Merah di Kabupaten Probolinggo: Sebuah Analisis Multiatribut Fishbein - Siti Qomariah; Ahmad Zainuddin (Benchmark, 2023)
The development of varieties in Probolinggo district is dynamic, indicating that farmers have their own preferences for shallot varieties. The shallot varieties developed in Probolinggo Regency are Biru Lancor and Batu Ijo. The purpose of this study was to determine farmers' preferences for shallot varieties in Probolinggo district. The sample used was 40 farmers. This research was analysed using fishbein multiattribute analysis. The results showed that farmers' preferences for shallot varieties in Probolinggo Regency were in favour of the Biru Lancor variety over Batu Ijo. The Biru Lancor variety excels at the attributes of hardness, spiciness, bulb colour, aroma, number of tillers, ease of marketing, seed price, stock quantity, and storability. While the Batu Ijo variety excels at the attributes of tuber shape, tuber size, plant height, harvest age, pest resistance, weather resistance, production yield, and productivity. Farmers are expected to use the biru lancor variety because it has the advantage of a large number of tillers and easy marketing.